Formation of the Competences “Initiative And Entrepreneurship” at the Lessons of History of Ukraine (10th Grade) - Halytska-Didukh, Tamara (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article examines the components and importance of forming one of the key competences “initiative and entrepreneurship” in the context of reforming modern secondary education; possibilities of its introduction in school historical education are determined on the basis of development of historical competence of students. The components of historical competence by integrating the economic dimension into the content of the tasks are highlighted. The subject “History of Ukraine” is focused on the formation of competence “initiative and entrepreneurship” through integration of inter-curriculum relations at the lesson of History of Ukraine, creative and activity approaches to the educational process. It is important not the accumulation of knowledge, but the ability to identify and analyze problems (including specific economic situations), to seek ways of their rational solution, to be able to think critically and to apply the acquired knowledge, skills and expertise to solve new problems. This is largely facilitated by active teaching methods that encourage students to be initiative, sociable, personally responsible; forms skills and abilities of non-standard problem-solving, independent choice of effective life strategies. The project method, which involves the ability to creatively apply the acquired knowledge in non-standard situations to solve various educational problems, should be noted separately; ability to find the necessary information independently; to work with different sources of information; develop group collaboration skills; ability to argue their own opinion, discuss other topics. An example is the subject of 10th grade projects that shape a given competence. Thus, forming the initiative and entrepreneurship competences at the lessons of History of Ukraine will contribute to the improvement of the students' overall vital competences, form in them the ability to creatively apply the acquired knowledge, skills and expertise to solve social problems, improve their well-being in non-standard life situations and conditions in general.